2021
DOI: 10.1371/journal.pone.0247998
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to daily use of the paretic upper limb in patients with chronic hemiparetic stroke–A retrospective cross-sectional study

Abstract: Aims The present study aimed to determine factors associated with the frequency of paralyzed upper extremity (UE) use in chronic stroke patients with severe UE functional deficiency. Methods We retrospectively reviewed the medical records of 138 consecutive patients, and 117 was analyzed (median age, 55 [range, 18–85] years; median stroke duration, 24.5 [range, 7–302] months) with chronic hemiparetic stroke who were admitted to our hospital for intensive upper extremity rehabilitation. The mean Fugl-Meyer As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Herein, ΔAOU and ΔQOM were identified as factors that mediate ΔFMA and ΔFIM (M) after stroke. It has been reported that upper limb usage improves ADL after stroke [ 26 ], and that upper limb function affects the frequency of upper limb use [ 6 ]. Furthermore, the relationship between upper limb function and ADL has been clarified in post-stroke hemiplegia [ 27 ], with Stevenson et al reporting that rehabilitation to increase the frequency of upper limb use improves upper limb function and ADL after stroke [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, ΔAOU and ΔQOM were identified as factors that mediate ΔFMA and ΔFIM (M) after stroke. It has been reported that upper limb usage improves ADL after stroke [ 26 ], and that upper limb function affects the frequency of upper limb use [ 6 ]. Furthermore, the relationship between upper limb function and ADL has been clarified in post-stroke hemiplegia [ 27 ], with Stevenson et al reporting that rehabilitation to increase the frequency of upper limb use improves upper limb function and ADL after stroke [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The upper limbs and hands play a key role in precise gripping, motor control, and the manipulation of objects ( Tonak et al, 2021 ) and have a significant impact on patients’ activities of daily living ( Tashiro et al, 2021 ). The upper limb and palm of the hand have high sensory thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, even in recent stroke rehabilitation, it is important to provide training to increase the frequency of use of paretic limbs. Research examining the factors associated with the frequency of paretic limb use in stroke patients found that both motor and sensory functions determine the contribution of paretic limbs to activities of daily living 18 , 19 . Furthermore, studies have highlighted the important role of paretic arm use in daily life with quantitatively evaluated changes in body ownership associated with decreased sensory and motor functions by measuring body-specific attention, which is defined as the amount of attention directed to the body 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%